Draft Annual Plan 2003-2004 Government of Mizoram - Planning Commission (Planning Commission, 2003)
INTRODUCTION: Mizoram is bounded on the north by the States of Assam and Manipur, on the east and south by Chin Hills of Myanmar and on the west by Chittagong Hill Tracts of Bangladesh and the State of Tripura. It covers an area of 21,087 Sq.Km. The hill areas of Mizoram enjoy cool temperate climate. The average annual rainfall is 217.5 cm. The temperature varies between 12 and 18 degrees Celsius in winter and 18 and 29 degree Celsius in summer.
Government of Mizoram